2005
DOI: 10.5194/nhess-5-1-2005
|View full text |Cite
|
Sign up to set email alerts
|

Near-seismic effects in ULF fields and seismo-acoustic emission: statistics and explanation

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects"Abstract. Preseismic intensification of fracturing has been investigated from occurrence analysis of seismo-acoustic pulses (SA foreshocks) and ULF magnetic pulses (ULF foreshocks) observed in Karimshino station in addition to seismic foreshocks. Such analysis is produced for about 40 rather strong and nearby isolated earthquakes during 2 years of recording. It is found that occurrence rate of SA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…1, the number of Es-spread observations is presented as function of the local time for "background" and "seismoactive" days separately. The seismo-active time interval of the two hours before midnight is in agreement with the results of the observation of ULF-fields connected with earthquakes (Molchanov et al 2004(Molchanov et al , 2005. By Molchanov et al (2004Molchanov et al ( , 2005) ULF variations of the magnetic field are found in the frequency region of 0.05-0.2 Hz.…”
Section: Observational Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…1, the number of Es-spread observations is presented as function of the local time for "background" and "seismoactive" days separately. The seismo-active time interval of the two hours before midnight is in agreement with the results of the observation of ULF-fields connected with earthquakes (Molchanov et al 2004(Molchanov et al , 2005. By Molchanov et al (2004Molchanov et al ( , 2005) ULF variations of the magnetic field are found in the frequency region of 0.05-0.2 Hz.…”
Section: Observational Resultssupporting
confidence: 78%
“…By Molchanov et al (2004Molchanov et al ( , 2005) ULF variations of the magnetic field are found in the frequency region of 0.05-0.2 Hz. The authors of the present work suggest that the increase of the Es-spread phenomena before earthquakes is caused by an enhanced activity of acoustic pulses with frequencies of the order of 0.05 Hz, which propagate from the region of earthquake preparation up into the atmosphere and ionosphere.…”
Section: Observational Resultsmentioning
confidence: 99%
“…A question arises immediately: what means earthquake preparation process in a large zone order of hundred kilometers as it is followed from abovementioned observational facts and from observation of nearseismic effects (e.g. Molchanov et al, 2004c)? It is evident that conventional seismology theories (nucleation, dilatancydiffusion, dilatancy instability, consolidation and so on) have failed to explain neither our results, nor seismic data itself (absence of large stress accumulation and dilatancy, existence of deep EQs etc.…”
Section: Discussionmentioning
confidence: 99%
“…(Svets et al, 2004;Biagi et al, 2003;Crowley and McCrea, 1988;Afraimovich, 2000); ii) Local such as atmospheric or underground explosions, volcanoes, extreme weather phenomena (Calais et al, 1998;Jacobson and Carlos, 1988;Afraimovich et al, 2000); iii) Earthquakes (Afraimovich et al, 2001;Molchanov et al, 2004;Molchanov et al, 2005;Meister et al, 2002;Liperovsky et al, 2002;Shvets et al, 2004).…”
Section: Introductionmentioning
confidence: 99%